Features of Surgical Correction of Spontaneous Luxation of the Complex “IOL Posterior Chamber – Capsular Bag” - O. P. Mishchenko; N. A. Senchenko; A. G. Shchuko (Acta Biomedica Scientifica)
Luxation of intraocular lens in capsular bag several years after cataract surgery leads to a decrease in visual function and requires surgical treatment.Aim: to determine effectiveness of various types of surgical treatment of late spontaneous dislocations of IOL in capsular bag.Methods. Analysis of 123 case histories of patients with late IOL dislocation, operated in 2013–2015, was made. First group included patients with replaced IOLs dislocated into pupillary lens. Second group consisted of patients who underwent reposition and suture of IOL to iris. Examination was made before operation and 6–12 months after operation. Results. The average term from moment of IOL implantation to its luxation was 8.78 ± 4.85 years. II degree of dislocation was detected in 74 % of patients, III degree of dislocation – in 10 %, and IV degree – in 16 % of patients.Uncorrected visual acuity was reduced to 0.15 ± 0.16; best corrected visual acuity to 0.31 ± 0.26. In 83.7 % of patients a pseudoexfoliation syndrome was detected. In 62.6 % of patients IOL luxation was accompanied byhydrodynamic disturbances. Best corrected visual acuity in period from 6 to 12 months after surgery was 0.40 ± 0.24, and after IOL reposition – 0.49 ± 0.22. In addition, after IOL replacement a significant increase in postoperative astigmatism was noted from –0.44 ± 0.84 to –1.96 ± 1.60 D (p < 0.001).Conclusion. As a result of surgical treatment of late spontaneous IOL dislocations in both groups increase in distance uncorrected and best corrected visual acuity was noted. Insufficient visual functions after surgical treatment were caused by concomitant pathology as well as increased postoperative astigmatism.